A Case Series that Supports the Application of the S2AI Technique for Fractures and Failures after Lumbosacral Fusion. Issue 2 (July 2020) - Weinreb, Jeffrey H.; Iweala, Uchechi; Matteini, Lauren E.; Yu, Warren D.; O'Brien, Joseph R.
Background: Sacral fractures and failures are uncommon after lumbosacral fusion but have received increasing attention in the surgical literature. They can be difficult to diagnose, making timely treatment difficult. No consensus has been reached on the characteristics of these complications or on optimal treatment. Questions/Purposes: The goal of this retrospective case series is to contribute additional cases of these uncommon complications of lumbosacral fusion to the surgical literature to help clinicians to anticipate, diagnose, characterize, manage, and treat sacral fractures and failures after lumbosacral fusion. Methods: The medical records of five patients who experienced a sacral fracture or failure after lumbosacral fusion between January 2012 and November 2017 were identified and reviewed retrospectively. Records were reviewed for age, sex, clinical presentation, previous management, outpatient clinical records, imaging, and post-operative course. Results: Four patients in the series experienced a sacral fracture and one experienced hardware failure. All patients presented with elevated pain and underwent revision surgery. Radiographic detection of the fracture or failure occurred at a mean of 11.2 weeks (range, 3 to 24 weeks) after initial surgery, and the mean age of patients was 68.2 years (range, 63 to 80 years). Of the five patients, four were female; two had been diagnosed with osteoporosis and two with osteopenia. In our case series, the S2–alar–iliac (S2AI) technique was used with success in all five cases. Conclusion: Fractures and failures after lumbosacral fusion can be difficult to diagnose because of delayed presentation, nonspecific presenting symptoms, and a lack of identifiable mechanism. A high index of suspicion is required to detect these uncommon complications, and patients have responded well to both conservative and surgical treatments.